Produktivitas nelayan tangkap jaring insang dasar dan hanyut selama covid-19 Di Kelurahan Napabalano Kecamatan Napabalano Kabupaten Muna - Piliana, Wa Ode; Gunawan, Fandy Rahmad; Lawelle, Sjamsu Alam; Yusuf, Sarini; Annaastasia, Nurhuda (Universitas Halu Oleo, 2023)
This study aims to determine the productivity of fisherman who use bottom gill nets and drift gill nets during the Covid-19 period. This research was conducted in Napabalano Village, Napabalano District, Muna Regency from April to May 2022. The sampling method used was the census method with the number of respondents being 8 bottom gill net fisherman and 8 drift gill net fisherman. Data was collected trough interviews, observation and documentation. Analysis of the data used is the productivity Analysis. The results of the study showed that the productivity obtained by bottom gill net fisherman averaged 2.42, meanwhile, the productivity obtained by drift gill net fisherman is 3.01 on average. Thus, the two fishing gears are declared productive because the average productivity value is >1.